Adolescent Risperidone treatment alters protein expression associated with protein trafficking and cellular metabolism in the adult rat prefrontal cortex. Issue 12 (16th May 2014) - Farrelly, Lorna A.; Dicker, Patrick; Wynne, Kieran; English, Jane; Cagney, Gerard; Föcking, Melanie; Cotter, David R.
<x xml:space="preserve">Abstract</x> The prefrontal cortex (PFC) is associated with mental health illnesses including schizophrenia, depression, bipolar disorder, and autism spectrum disorders. It richly expresses neuroreceptors which are the target for antipsychotics. However, as the precise mechanism of action of antipsychotic medications is not known, proteomic studies of the effects of antipsychotic drugs on the brain are warranted. In the current study, we aimed to characterize protein expression in the adult rodent PFC (n = 5 per group) following low‐dose treatment with Risperidone or saline in adolescence (postnatal days 34–47). The PFC was examined by triplicate 1 h runs of label‐free LC‐MS/MS. The raw mass spectral data were analyzed with the MaxQuantTM software. Statistical analysis was carried out using SAS® Version 9.1. Pathway and functional analysis was performed with IngenuityPathway Analysis and in the Database for Annotation, Visualization and Integrated Discovery (DAVID), respectively, the most implicated pathways were found to be related to mitochondrial function, protein trafficking, and the cytoskeleton. This report adds to the current repertoire of data available concerning the effects of antipsychotic drugs on the brain and sheds light on their biological mechanisms. The MS data have been deposited with the ProteomeXchange Consortium with dataset identifier PXD000480.